2022
DOI: 10.1021/jacs.1c13399
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy for the Synthesis of Rare Sugars via Ru(II)-Catalyzed and Boron-Mediated Selective Epimerization of 1,2-trans-Diols to 1,2-cis-Diols

Abstract: Human glycans are primarily composed of nine common sugar building blocks. On the other hand, several hundred monosaccharides have been discovered in bacteria and most of them are not readily available. The ability to access these rare sugars and the corresponding glycoconjugates can facilitate the studies of various fundamentally important biological processes in bacteria, including interactions between microbiota and the human host. Many rare sugars also exist in a variety of natural products and pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 79 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Salvage synthesis involves phosphorylation of the monosaccharide using a kinase and pyrophosphorylation by a pyrophosphorylase . However, only very few natural sugar nucleotides can be prepared by salvage synthesis, as most naturally occurring monosaccharides are not readily available and their chemical syntheses are extremely difficult. Moreover, the lack of suitable kinases or pyrophosphorylases is another issue. Alternatively, de novo biosynthesis from existing common sugar nucleotides produces the majority of sugar nucleotides in nature. The process involves single or multiple reactions including dehydration, isomerization, epimerization, oxidation, reduction, amination, and acetylation reactions. Nevertheless, it is widely accepted that such complicated bioconversions are not practical for synthetic use due to the complex reaction routes, great purification difficulties, and high preparation cost.…”
Section: Introductionmentioning
confidence: 99%
“…Salvage synthesis involves phosphorylation of the monosaccharide using a kinase and pyrophosphorylation by a pyrophosphorylase . However, only very few natural sugar nucleotides can be prepared by salvage synthesis, as most naturally occurring monosaccharides are not readily available and their chemical syntheses are extremely difficult. Moreover, the lack of suitable kinases or pyrophosphorylases is another issue. Alternatively, de novo biosynthesis from existing common sugar nucleotides produces the majority of sugar nucleotides in nature. The process involves single or multiple reactions including dehydration, isomerization, epimerization, oxidation, reduction, amination, and acetylation reactions. Nevertheless, it is widely accepted that such complicated bioconversions are not practical for synthetic use due to the complex reaction routes, great purification difficulties, and high preparation cost.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the absence of the boronate trapping agent, this catalyst system can be used to epimerize axial alcohols into equatorial alcohols, as was shown for galactosides ( Scheme 1 C). 20 Finally, it was recently shown that direct epimerization of 1,2-trans to 1,2-cis diols in partly protected carbohydrates can be achieved with boron-mediated ruthenium-catalyzed hydrogen-borrowing/hydrogen transfer reactions, see the work of W. Tang et al 21 It will not be trivial, if possible at all, to dissect for all these reactions the kinetic and thermodynamic contribution to the observed regio- and stereoselectivity. To give an example, it has been shown by thorough computational studies using relativistic density functional theory that palladium-catalyzed oxidation in pyranoses preferentially takes place at C3 because the ring oxygen impedes the build-up of positive charge at C2 and C4 going to the transition state.…”
Section: Discussionmentioning
confidence: 99%
“…Their roles in biological systems range from being major sources of energy, providing structural solidity as well as their roles in cell membrane. Saccharides also find several applications in pharmaceutical, textile, food, and chemical industries. In addition, there has recently been an increased interest in “rare” sugars regarding their large-scale synthesis, characterization, and application. That is, although there are abundant natural sources for commonly used sugars (e.g., d -glucose, d -fructose, and sucrose, to name just a few), ,, most other sugars are naturally rare, and there are hundreds of them. Due to their limited natural sources, the rare sugars must be prepared from their biomass precursors through multistep chemical or enzymatic syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…The recent interest in rare sugars is rekindled by their observed superior biological activity, which has been demonstrated in a wide range of areas, including their use in antiaging, low-caloric sweeteners, ,, and nonsteroidal anti-inflammatory drugs for arthritis and renal inflammatory disorders . Often, the synthetic methods to prepare some rare sugars simply involve an isomerization process, thus making their characterization very challenging. Take sucrose as an example.…”
Section: Introductionmentioning
confidence: 99%